2020
DOI: 10.3390/ma13194308
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Electrical, and Thermal Properties of Carbon Nanotube Buckypapers/Epoxy Nanocomposites Produced by Oxidized and Epoxidized Nanotubes

Abstract: High volume fraction carbon nanotube (CNT) composites (7.5–16% vol.) were fabricated by the impregnation of CNT buckypapers into epoxy resin. To enhance the interfacial reaction with the epoxy resin, the CNTs were modified by two different treatments, namely, an epoxidation treatment and a chemical oxidation. The chemical treatment was found to result in CNT length severance and to affect the porosity of the buckypapers, having an important impact on the physico-mechanical properties of the nanocomposites. Ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…As a result, the densification of the CNT networks caused by the hot press at 70 °C played a crucial role in improving the thermal conductivities, promoting 2.473 W/m·k. A similar conclusion was reached in the study by Trakakis [ 46 ], where it was found that the thermal conductivity increased with decreasing porosity. In addition, the thermal conductivity of composites reinforced by CNTs was affected by many factors, such as defects, phonon scattering, filler type, structure, functionalization, alignment, and network formation [ 47 ].…”
Section: Resultssupporting
confidence: 88%
“…As a result, the densification of the CNT networks caused by the hot press at 70 °C played a crucial role in improving the thermal conductivities, promoting 2.473 W/m·k. A similar conclusion was reached in the study by Trakakis [ 46 ], where it was found that the thermal conductivity increased with decreasing porosity. In addition, the thermal conductivity of composites reinforced by CNTs was affected by many factors, such as defects, phonon scattering, filler type, structure, functionalization, alignment, and network formation [ 47 ].…”
Section: Resultssupporting
confidence: 88%
“…The prepreg was compression-molded using a hydraulic press. Since prepregs have become the main raw materials in the composites industry, this technique can be applied in composites science and technology for new materials with a combination of tailored mechanical, electrical, and thermal properties [ 100 , 101 ].…”
Section: Fabrication Technique Involved In Carbon Nanotube Polymermentioning
confidence: 99%
“…The introduction of CNTs into a polymer matrix lowers the percolation threshold because the nanotubes are covalently incorporated into the polymer cross-linked structure. This network structure of fillers create conductive paths where the CNTs are in close contact to each other, thus facilitating the conduction of electron through ‘hopping’ or ‘tunnelling’ mechanisms [ 100 ]. Therefore, with increased volume fractions of CNTs, the network paths intensify and hence abruptly increase the conductivity of reinforced polymer matrices.…”
Section: Performance Of Carbon Nanotube–polymer Compositesmentioning
confidence: 99%
See 2 more Smart Citations